Influence of ovariectomy combined with lack of masticatory force in the evolution of periodontal disease - Noala Vicensoto Moreira Milhan; Lilibeth Ferraz de Brito Penna Forte; Luana Marotta Reis de Vasconcelos; Ivan Balducc; Yasmin Rodarte Carvalho (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the influence of ovariectomy combined with lack of masticatory force in the evolution of periodontal disease induced in rats. Methods: Forty rats were bilaterally ovariectomized and 40 were submitted to sham ovariectomy. Periodontal disease was induced in the mandibular left first molar and the maxillary left first molar was extracted from half of the rats. The rats were randomly euthanized at 3, 7, 14 and 30 days post periodontal disease induction. Serial sections were obtained from the furcation area and stained for histological and histomorphometric analysis. The results of the histomorphometric analysis were statistically analyzed by ANOVA and Tukey tests. Results: The results demonstrated statistically significant differences in the percentage of bone tissue when the variables presence or absence of estrogen (p=0.020) and time of euthanasia (p=0.002) were evaluated. However, the extraction procedure did not significantly affect the percentage of bone tissue (p=0.598). Conclusions: The bone loss resulting from periodontal disease is increased by estrogen deficiency and varies according to the time course of periodontitis. In contrast, masticatory force does not seem to interfere in bone loss derived from periodontal disease.